2012
DOI: 10.1308/147363512x13311314197176
|View full text |Cite
|
Sign up to set email alerts
|

Training in Current Medical Education: Surgeons are Different from Their Medical Colleagues

Abstract: Education and training in surgery have focused on an apprenticeship style of learning, particularly in the operating theatre, with little emphasis on understanding how trainees learn. This focus on one style of training may not achieve the best possible outcomes. The need to deliver training over a shorter period since the introduction of the European WorkingTime regulations makes each learning opportunity vital. Learning styles have already been suggested as an important issue in obstetrics and gynaecology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…(13,14) Studies in general surgery have shown that the predominant learning styles of surgical trainees is activist and pragmatist, i.e they learn by doing, involve themselves fully and without bias in new experiences, they try out new ideas, theories and techniques to see if they work. (13)(14)(15) Our study demonstrated that the main learning styles of surgeons are reflector and theorist, 90% and 80% respectively. These two learning styles were also predominant among physicians, 90% each.…”
Section: Discussionmentioning
confidence: 64%
“…(13,14) Studies in general surgery have shown that the predominant learning styles of surgical trainees is activist and pragmatist, i.e they learn by doing, involve themselves fully and without bias in new experiences, they try out new ideas, theories and techniques to see if they work. (13)(14)(15) Our study demonstrated that the main learning styles of surgeons are reflector and theorist, 90% and 80% respectively. These two learning styles were also predominant among physicians, 90% each.…”
Section: Discussionmentioning
confidence: 64%
“…3 Although the present study did not specifically evaluate these factors, these characteristic converging and accommodating learning styles of surgical trainees may account for the residents in the present study preferring the new learning interface. Osborne et al 4 compared the learning styles of 27 surgical and 20 medicine trainees and found that surgical trainees had a significantly higher proportion of those that preferred active learning both demonstrations, examples, and self-assessed activities, whereas medicine trainees preferred styles that discussed instructions, debated management, and held regular formalized reflections.…”
Section: Innovative Teaching Strategies For Surgery Resident Education Sessions: Learner Preference Of Slide-based Presentations Versus Fmentioning
confidence: 99%
“…Honey and Mumford also identified learners as activists, reflectors, theorists and pragmatist style learners [ 11 ]. Not surprisingly surgical trainees are most commonly activists or pragmatists who learn through practical tasks and experiments [ 12 ].…”
Section: Introductionmentioning
confidence: 99%